Strategies for navigating primary scientific literature in undergraduate immunology courses - Bergerson, Rachel J.; Basta, Holly A.; Coleman, Sean T.; Pandey, Sumali (Frontiers in Education, 2025)
The impact of immunology on our daily lives is growing every year. From vaccines to immunotherapies, it's essential for our healthcare professionals (present and future) and the general public as patients or caregivers to be literate in immunology. One way to foster immune literacy in this rapidly advancing field is through Primary Scientific Literature (PSL). There are unique challenges with integrating PSL into immunology courses. First, the laboratory techniques used are often new and not things students have tried before or may have access to, such as flow cytometry. Second, the tools used in this literature can be confusing. For example, antibodies are often used as both part of the research method and as the research subject. Third, immunology literature is especially heavy in acronyms, jargon and abbreviations. In this manuscript, four instructors gathered to discuss the strategies that they have used in their classrooms to utilize PSL in immunology (PSL-I) and scaffold various activities around it. These teaching methods vary from highlighting immunology-specific techniques, interpreting figures, alignment with the 5E instructional model to guide an inquiry, jigsaw format learning, to in-depth journal-club style analysis. Finally, this paper discusses reflections from our experiences teaching PSL-I. We know that there are misconceptions about immunology and health in general. If we teach PSL and how to interpret it, we hope to prepare our students not just for their chosen field, but also to think critically and discern facts from fiction in society.